2014
DOI: 10.1007/s00109-014-1139-0
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 regulates the cigarette smoke-induced signalling in rheumatoid arthritis synovial fibroblasts

Abstract: Cigarette smoke induces pro-inflammatory and matrix-destructive responses in RASF. Cigarette smoke enhances the expression of SIRT6 in vitro and in vivo. TNFα increases the levels of SIRT6. SIRT6 diminishes MMP1 production under cigarette smoke extract and TNFα stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…However, when exposed to risk factors, such as smoking or ageing, Sirt3 knockout mice will have high oxidative stress level and may be more sensitive to osteoporosis Among the Sirtuin family, Sirt1, Sirt2, and Sirt6 are reported to regulate bone homeostasis in vivo [24][25][26]. Sirt1 regulates differentiation of MSCs and represses osteoblast injury [27,28], while Sirt2 and Sirt6 protect mice from arthritis [25,26]. Sirt3 is the first mitochondrial Sirtuin that has been shown to participate in maintaining bone hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, when exposed to risk factors, such as smoking or ageing, Sirt3 knockout mice will have high oxidative stress level and may be more sensitive to osteoporosis Among the Sirtuin family, Sirt1, Sirt2, and Sirt6 are reported to regulate bone homeostasis in vivo [24][25][26]. Sirt1 regulates differentiation of MSCs and represses osteoblast injury [27,28], while Sirt2 and Sirt6 protect mice from arthritis [25,26]. Sirt3 is the first mitochondrial Sirtuin that has been shown to participate in maintaining bone hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…To induce lung emphysema and COPD in an animal model, mice were exposed to cigarette smoke from research cigarettes (1R4F, University of Kentucky, USA) for 5 days per week as described elsewhere [16]. After 3 weeks mice were euthanized and total RNA including miRNAs from lung tissue was isolated.…”
Section: Experimental In Vivo Modelsmentioning
confidence: 99%
“…Similarly, Sirt6 suppresses inflammation and bone resorption in the CIA model [67•]. Consistently, Engler et al showed that cigarette smoking, a risk factor for RA development, increased SIRT6 levels in RA synovial fibroblasts and correlated with attenuated MMP-1 production [68], supporting the anti-inflammatory effects exerted by SIRT6.…”
Section: Sirt2-7 In Oa and Cartilage Biologymentioning
confidence: 72%